2024
DOI: 10.3390/curroncol31020057
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to Date on the Therapeutic Potential of Zolbetuximab in Advanced Gastroesophageal Adenocarcinoma

Jane E. Rogers,
Jaffer Ajani

Abstract: Gastric adenocarcinoma (GAC) continues to be a prevalent worldwide malignancy and a leading cause of cancer death, and it is frequently cited as incurable. Targeted therapy in GAC has lagged behind other solid tumors. The human epidermal growth factor receptor-2 (HER-2) represented the single target in GACs for many years, seen in approximately 20% of patients with advanced GAC. Recent advances in management now include the addition of immunotherapy checkpoint inhibition to select front-line advanced GACs. Unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It has been observed that 14-87% of gastric adenocarcinoma patients express CLDN18.2. Since CLDN18.2 is expressed on the outer cell membrane, it is accessible for binding with monoclonal antibodies (mAbs) [85].…”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…It has been observed that 14-87% of gastric adenocarcinoma patients express CLDN18.2. Since CLDN18.2 is expressed on the outer cell membrane, it is accessible for binding with monoclonal antibodies (mAbs) [85].…”
Section: Therapeutic Targetsmentioning
confidence: 99%